2019
DOI: 10.1111/1471-0528.15623
|View full text |Cite
|
Sign up to set email alerts
|

Non‐obstetric causes of severe maternal complications: a secondary analysis of the Nigeria Near‐miss and Maternal Death Survey

Abstract: Objective To evaluate the burden, causes and outcomes of severe non-obstetric maternal complications in Nigerian public tertiary hospitals.Design Secondary analysis of a nationwide cross-sectional study.Setting Forty-two tertiary health facilities.Population Women admitted with complications during pregnancy, childbirth or puerperium.Methods All cases of severe maternal outcome (SMO: maternal near-miss or maternal death) due to non-obstetric causes were prospectively identified over a 1-year period. Maternal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
2
11
2
Order By: Relevance
“…In the review of the main causes of extreme maternal morbidity, we found hypertensive disorders in first place with 57% followed by obstetric hemorrhage with 29%, which coincides with that reported by other authors in Latin America [17] and Morocco [18], although it is worth mentioning that it is different to that reported by other authors who mention as a first cause of extreme maternal morbidity to be obstetric hemorrhage [19][20][21][22]. This coincides with the high incidence of pre-eclampsia in our country along with the fact that in our study, no maternal deaths were registered, and demonstrates that even though morbidity due to this pathology has not decreased, the established management in our hospital has had an impact on reducing the rate of maternal deaths and reinforces the need to maintain close surveillance of these patients (Table 6).…”
Section: Discussionsupporting
confidence: 83%
“…In the review of the main causes of extreme maternal morbidity, we found hypertensive disorders in first place with 57% followed by obstetric hemorrhage with 29%, which coincides with that reported by other authors in Latin America [17] and Morocco [18], although it is worth mentioning that it is different to that reported by other authors who mention as a first cause of extreme maternal morbidity to be obstetric hemorrhage [19][20][21][22]. This coincides with the high incidence of pre-eclampsia in our country along with the fact that in our study, no maternal deaths were registered, and demonstrates that even though morbidity due to this pathology has not decreased, the established management in our hospital has had an impact on reducing the rate of maternal deaths and reinforces the need to maintain close surveillance of these patients (Table 6).…”
Section: Discussionsupporting
confidence: 83%
“…MDs were also associated with lack of awareness, lower and elderly ages. Consequently, it led to poorer pregnancy outcomes [32]. Similar findings were observed in another study in which the association of anemia with maternal and neonatal outcomes was investigated.…”
Section: Non-obstetric Causes Of Mdssupporting
confidence: 78%
“…It was observed that 9.4% (9401/100107) women admitted to the 42 tertiary hospitals in Nigeria for maternal complications had non-obstetric reasons. 4% (375/9401) of these complicated cases were MNM in 48% (183/375) and MD in 51.2% (192/375) [32]. Severe anemia contributed to 61.2% of MNM and 32.8% of MDs.…”
Section: Non-obstetric Causes Of Mdsmentioning
confidence: 98%
“…Non obstetric causes found to be related to adverse maternal outcome were anaemia unrelated to haemorrhage, cancer, hepatic disease, neurological and CVS dysfunction. 7 In a study maternal near miss and death associated with abortive pregnancy outcome, it was found that 78 maternal death and 366 near miss occurred from abortion and ectopic pregnancy in 42 Nigerian referral hospitals in 1 year. 8 In our set up also, major causes of near miss are hypertensive disorder and obstetric haemorrhage but these cases are being highlighted as they presented as diagnostic dilemma and were a therapeutic challenge.…”
Section: Discussionmentioning
confidence: 99%